Impact of Diabetes on Clinical Characteristics and Angiographic findings in Young Adults with ST-Elevation Myocardial Infarction: A Cross-sectional Study - Abhishek Golla; Mohammed Hidayathulla; Sowmya Deepthi Chavala; Rajashekar R Gurrala; Hussain Bangi (Journal of Clinical and Diagnostic Research)
Introduction: The prevalence of diabetes among young patients with ST-Elevation Myocardial Infarction (STEMI) is increasing, but its impact on this population remains understudied. Limited data on diabetes in young patients with STEMI exist. The presence of diabetes among young patients experiencing STEMI deserves special consideration, as it manifests with unique clinical patterns and can significantly impact their active lifestyle. Aim: To determine the effect of diabetes and associated clinical characteristics in young patients with STEMI. Materials and Methods: A cross-sectional study was conducted at a tertiary care centre in India between April 2018 and December 2019. Fifty-one STEMI patients aged below 40 years were enrolled and categorised into diabetic (n=23) and non diabetic (n=28) groups based on glycated haemoglobin (HbA1c) levels. Clinical characteristics, laboratory parameters and angiographic findings were compared between the groups. This study analysed continuous variables using Student’s t-test and Analysis of Variance (ANOVA) (expressed as mean±SD), and categorical variables using Chi-square or Fisher’s exact tests (shown as n, %). A p-value of <0.05 was considered significant. Results: The mean age was 35.6±3.4 years, with 80.4% male predominance. Diabetic patients showed higher prevalence of dyslipidaemia (p-value=0.009), hypertension (p-value=0.043), and metabolic syndrome (p-value=0.002). They also exhibited significantly higher levels of total cholesterol, triglycerides and Low-Density Lipoprotein Cholesterol (LDL-C). Anterior Wall Myocardial Infarction (AWMI) was predominant in both groups (p-value=0.442). Single-Vessel Disease (SVD) was most common, but Triple-Vessel Disease (TVD) was observed exclusively in diabetic patients (p-value=0.198). The Left Anterior Descending (LAD) artery was the most involved vessel in both groups. Conclusion: Compared to non diabetic patients, young STEMI patients with diabetes demonstrated a more adverse cardiovascular risk profile and lipid abnormalities.